Western Balkans in the European Union Policy (Economic and Political Thought, 2010)
In the present article, the author analyzes the position of the WestBalkans in the European Union policy, wondering about the directions of itsdevelopment, and presenting and analyzing the methods of its implementationas well as the planned and achieved objectives. At the same time he attemptsto present attitudes of individual countries’ societies of the region towardsthe European Union, highlighting the specific aspect of development offunctional regional co-operation.